The impact of mobile money on macroeconomic development: insights from Côte d'Ivoire - Payaneeandee, Mary Catherine Sonia, (Graduate School of Business (GSB), 2025)
Mobile money has contributed to financial inclusion across African countries. Indeed, mobile money has proven immense economic benefits to developing countries and is a driving force behind numerous economic activities. However, there are concerns that mobile money may perhaps weaken financial stability. The consequences of mobile money on these macroeconomic indicators such as: inflation, interest spread rates, money stock, private-sector credit, and economic aggregate activity are intriguing. Côte d'Ivoire is viewed as the most robust financial state within the African continent and mobile money has evolved rapidly across the country. As such, this gives room to prospect the consequences of mobile money on macroeconomic development in Côte d'Ivoire. Indeed, the core idea of this analysis is to evaluate the repercussion of mobile money on macroeconomic development in Côte d'Ivoire. The study adopted a time series approach, making use of monthly data from January 2013 till December 2021. The economic investigation adopts the structural vector autoregressive (SVAR) to analyse the data. The results showed moderate effect on the macroeconomic development variables in Côte d'Ivoire. Specifically, the shocks involving mobile money may take time to impact productivity but nonetheless support economic aggregate activity in the country. Mobile money seems to not cause inflationary pressures. In the case of money stock, mobile money leads to a shift from non-financial assets to financial assets thus influencing money supply. Furthermore, mobile money may take time to influence supply of private credit but remains an essential tool for the supply private credit. As for interest spread rates, a positive impact is noticed, and remain relatively stable. Regarding the conduct of monetary policy, mobile money has moderate impact on monetary policy transmission mechanisms, monetary effects take longer to gain full potential in Côte d'Ivoire.